Perancangan Sistem Agenda Kegiatan Bulanan Berbasis Web Di Telkom Daman Gaharu - Ony Hizri Kaifa Purba; Rinanda Putri Rambe; Muhammad Ikhsan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
A monthly agenda is a tool used to plan, coordinate and monitor planned and executed actions aimed at achieving organizational or personal goals. Until now, DAMAN Telkom Gaharu Medan still makes monthly agendas in a time-consuming and ineffective way, namely by sending letters or invitations and other materials. Therefore, DAMAN Telkom Gaharu Medan has developed a web-based employee monthly agenda information system which can make it easier to prepare monthly agendas and can be accessed by all workers. The system has the following features: employee monthly agenda, home, admin, login, and print data. By utilizing text editors such as Notepad++, Sublime, etc., together with xampp software, the concept of this information system was developed. The ADDIE method which combines analysis, design, development, implementation and evaluation is used in the system design development process. System design, menu design, coding, and testing are several stages that constitute the development stages of an information system design. The ability to display monthly agenda data on DAMAN Telkom Gaharu Medan is the final result of developing a web-based monthly agenda information system. In order to improve employee performance at DAMAN Telkom, Gaharu Medan will make it easier for workers to access the monthly agenda online.